2014
DOI: 10.1158/1078-0432.ccr-14-0246
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptional Alterations in Lung Adenocarcinoma in Relation to Smoking History

Abstract: Purpose: Cigarette smoking is the major pathogenic factor for lung cancer. The precise mechanisms of tobacco-related carcinogenesis and its effect on the genomic and transcriptional landscape in lung cancer are not fully understood.Experimental Design: A total of 1,398 (277 never-smokers and 1,121 smokers) genomic and 1,449 (370 never-smokers and 1,079 smokers) transcriptional profiles were assembled from public lung adenocarcinoma cohorts, including matched next-generation DNA-sequencing data (n ¼ 423). Unsup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Combined with similar findings of intrinsically heterogeneous gene expression and CNA patterns in smoking-defined adenocarcinoma subgroups (20,31), our results question whether never-smokers can be identified as a molecular subgroup of its own with transcriptional, DNA methylation, and CNA patterns clearly different from tumors arising in smokers. Instead, our study further supports that a majority of adenocarcinomas arising in never-smokers together with a specific subset of tumors from smokers represent a more distinct and relevant molecular/biologic entity of less aggressive and potentially more smoking-unrelated disease (20,31). The clinical smoking definitions are intrinsically problematic due to their self-reported nature, but also because they do not capture the intensity and duration of cigarette exposure, and the exposure to environmental tobacco smoke and other pollutants for never-smokers.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Combined with similar findings of intrinsically heterogeneous gene expression and CNA patterns in smoking-defined adenocarcinoma subgroups (20,31), our results question whether never-smokers can be identified as a molecular subgroup of its own with transcriptional, DNA methylation, and CNA patterns clearly different from tumors arising in smokers. Instead, our study further supports that a majority of adenocarcinomas arising in never-smokers together with a specific subset of tumors from smokers represent a more distinct and relevant molecular/biologic entity of less aggressive and potentially more smoking-unrelated disease (20,31). The clinical smoking definitions are intrinsically problematic due to their self-reported nature, but also because they do not capture the intensity and duration of cigarette exposure, and the exposure to environmental tobacco smoke and other pollutants for never-smokers.…”
Section: Discussionsupporting
confidence: 68%
“…The TCGA consensus clusters were derived by unsupervised consensus clustering of the most varying genes (SD of variation across tumors >1) using a three-group solution as described in ref. (31). P values were calculated using the c 2 test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Vucic et al9 found that microRNAs disrupted in a smoking status-dependent manner affected distinct cellular pathways and differentially influenced lung cancer patient prognosis in current, former, and never smokers. Moreover, Karlsson et al10 identified some genomic and transcriptional alterations in lung adenocarcinoma in relation to smoking history. In spite of these findings, we think it is not enough in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the genomic landscape of NSCLC has been extensively investigated (2)(3)(4). However, for the majority of NSCLC patients, treatment options are still limited, and the overall prognosis remains poor.…”
Section: Introductionmentioning
confidence: 99%